2014
DOI: 10.1039/c4cy00733f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the catalytic cracking of naphtha over ZSM-5 zeolite: effect of reduced crystal size on the reaction of naphthenes

Abstract: The catalytic cracking of model naphthenes (cyclohexane and methylcyclohexane) over ZSM-5 zeolites of different crystal sizes (macro and nanoZSM-5) was examined at reaction temperatures ranging from 748 to 923 K under atmospheric pressure, focusing on the associated reaction rate constants and activation energies. The catalytic cracking was found to follow first-order kinetics with respect to the naphthene concentrations and the activation energies for cyclohexane and methylcyclohexane cracking over nanoZSM-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The enhanced activity, selectivity, and stability of hierarchical zeolites have often been attributed to reduced transport limitations and increased accessibility to active sites as a result of added meso‐ and macropores. However, despite the significant effort devoted to the design of new hierarchical zeolites, limited progress has been achieved for quantitatively establishing the link between the observed performance and the hierarchical structure . Such quantitative connection between the structural characteristics and the catalytic behavior could lead to the rational design of improved catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced activity, selectivity, and stability of hierarchical zeolites have often been attributed to reduced transport limitations and increased accessibility to active sites as a result of added meso‐ and macropores. However, despite the significant effort devoted to the design of new hierarchical zeolites, limited progress has been achieved for quantitatively establishing the link between the observed performance and the hierarchical structure . Such quantitative connection between the structural characteristics and the catalytic behavior could lead to the rational design of improved catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, catalytic cracking of naphtha into light alkenes has been attracting extensive attention owing to its advantages in product control and energy conservation . According to the reported catalyst candidates, ZSM‐5, containing abundant protonic sites, has been considered as one of the most promising ones for this process . However, the catalytic applications of ZSM‐5 zeolites are limited by mass transport in the microporous network if bulky molecules are involved in the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] According to the reported catalyst candidates, ZSM-5, containing abundant protonic sites, has been considered as one of the most promising ones for this process. [7,8] However,t he catalytic applications of ZSM-5 zeolitesa re limited by mass transport in the microporous network if bulky molecules are involved in the reaction. [9][10][11][12][13] In this regard,t he introduction of mesopores into microporous zeolites to obtain hierarchical ones,p ossessing the catalytic features of microporosity andt he improved mass transport consequence of mesoporosity, [14][15][16][17][18][19][20] would be an optimal choice for better performance.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of the catalytic cracking of the (model) naphtha compounds cyclohexane, methylcyclohexane and n-heptane over ZSM-5 has been studied by Konno et al 52 The catalytic cracking was found to follow first-order kinetics with respect to the alkane concentrations and the activation energies for cyclohexane, methylcyclohexane and n-hexane cracking over nano-ZSM-5 (crystal size = 100 nm) were determined to be 119, 116 and 126 kJ mol À1 , respectively, which are significantly higher compared to the conventional catalyst (macro-ZSM-5; crystal size = 2 mm). In order to elucidate the rate-limiting step in the cracking process, the Thiele modulus and the effectiveness factor were determined.…”
Section: Catalytic Crackingmentioning
confidence: 99%